Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.31235/osf.io/9yxaq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Teacher Morale and Mental Health at the Conclusion of the COVID-19 Pandemic

Abstract: As teachers entered the 2021-2022 school year, schools tasked teachers with the challenge of closing the learning loss gap, maintaining the same standards as a typical school year, implementing COVID-19 safety protocols, and teaching to grade-level grades standards. The current study used the theoretical framework of teacher demoralization to explore teacher morale and mental health at the end of the 2021-2022 school year. The sample included 830 PK-12 individual teachers from across the United States. Analysi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…This timing could have impacted the results in several ways. For example, educator morale and mental health were low during this time (Pressley et al, 2022) and some special educators reported that COVID-19 created additional job stress, both of which could have caused teachers to respond more negatively than they would have responded in non-pandemic years. Furthermore, some special educators indicated that COVID-19 negatively impacted their ability to write IEPs collaboratively; thus, the results related to collaboration may not be reflective of educators' practices when schools are operating in a fully in-person format.…”
Section: Limitationsmentioning
confidence: 99%
“…This timing could have impacted the results in several ways. For example, educator morale and mental health were low during this time (Pressley et al, 2022) and some special educators reported that COVID-19 created additional job stress, both of which could have caused teachers to respond more negatively than they would have responded in non-pandemic years. Furthermore, some special educators indicated that COVID-19 negatively impacted their ability to write IEPs collaboratively; thus, the results related to collaboration may not be reflective of educators' practices when schools are operating in a fully in-person format.…”
Section: Limitationsmentioning
confidence: 99%
“…There are opposing views on the necessity of collecting race-based data within the U.S. government. However, in mid-April, 2020, the Congressional Black Caucus introduced legislation, The Equitable Data Collection and Disclosure on COVID-19 Act , to ensure that the Department of Health and Human Services would begin to collect and post essential demographic data such as race, ethnicity, sex, age, and socioeconomic and disability status, daily on the Centers for Disease Control and Prevention website along with COVID-19-related testing, treatment, and outcomes (Atkins, 2020; Pressley, 2020). As of early June, 2020, states were required to report COVID-19 data by race and ethnicity, which is essential for the identification of community needs and the best ways to allocate vital resources (Shelton, 2020).…”
Section: Owning the Pastmentioning
confidence: 99%
“…The pandemic has raised widespread concern and presented unprecedented challenges for educational institutions (Oducado, 2020). Apart from the obvious risks to physical health, the psychological impact of COVID-19 also carries significant threats and dangers to mental health and well-being as higher levels of anxiety and stress are further exacerbated by the uncertainty of the situation (Pressley et al, 2022;Rabacal et al, 2020;Santiago et al, 2023). In the advent of the pandemic, there was a significant decline in the mental health and well-being of teachers due to various additional demands present in their work environment.…”
Section: Introductionmentioning
confidence: 99%